Influencing Organisational Buying Process: Antecedents, Dimensions And Consequences - Loo, Mark Kam Loon (2007)
This research shows that maangers can exploit this comprehensive antecedents-dimensions-consequences framework to influence the buying process more effectively. They can incorporate the identified significant variables at each buy stage to influence decision making. They can raise the level of marketing effectiveness by heeding two critical findings: (1) improve marketing effortsat the Purchase buy stage, the only buy stage found to influence Loyalty significantly, and (2) enhance e-commerce, identified as a significant influencer at the Search and Post Purchase buy stages.